Palestinian Christians in the Israeli state. (Taylor & Francis, 2012)
Although Christians form a significant proportion of the Palestinian Arab minority in Israel, very little research has, until now, been undertaken to examine their complicated position within Israel. This book demonstrates the limits of analyses which characterise state-minority relations in Israel in terms of a so-called Jewish-Muslim conflict, and of studies which portray Palestinian Christians as part of a wider exclusively religious-based transnational Christian community. This book locates its analysis of Palestinian Christians within a broader understanding of Israel as a Jewis.